Prevalence of nursing diagnoses in an intensive care unit - Vinicia de Holanda Cabral; Ítalo Rigoberto Cavalcante Andrade; Elizabeth Mesquita Melo; Tatiana de Medeiros Colletti Cavalcante (Rev Rene)
Objective: to identify the main nursing diagnostic titles used in the care of critically ill patients hospitalized in an Intensive Care Unit, verifying the presence thereof in the diagnoses of NANDA International’s Taxonomy II. Methods: descriptive and documental study, in which 69 medical records of patients aged over 18 years were consulted. Results:22 nursing diagnostic titles were found; the most frequent was risk for infection (99.0%), risk for skin integrity (75.0%) and risk for aspiration (61.0%). Most diagnoses were in the domains safety/protection (43.0%) and activity/rest (26.5%). Conclusions: authors identified the main nursing diagnostic titles used in the care of critically ill patients admitted to the Intensive Care Unit and the presence thereof in the diagnoses of NANDA International’s Taxonomy II.